We can use the inverse function derivative theorem:
![\frac{\textrm{d}f^(-1)}{\textrm{d}x}\Big\vert_(x=a) = \frac{1}{\frac{\textrm{d}f}{\textrm{d}x}\Big\vert_(x=f^(-1)(a))}.](https://img.qammunity.org/2021/formulas/mathematics/college/mce7n03zt2ccb5wr1ynkqwq2vjysf7xjjz.png)
In this case, we want to evaluate
, so:
![\frac{\textrm{d}f^(-1)}{\textrm{d}x}\Big\vert_(x=1) = \frac{1}{\frac{\textrm{d}f}{\textrm{d}x}\Big\vert_(x=f^(-1)(1))}.](https://img.qammunity.org/2021/formulas/mathematics/college/o0kkudp1n8rvkbabsczhyfbj23z2fwpx2x.png)
The derivative is:
![\frac{\textrm{d}f}{\textrm{d}x} = \frac{\textrm{d}}{\textrm{d}x}\left[\ln(8x + \textrm{e})\right] = \frac{1}{8x+\textrm{e}}\frac{\textrm{d}}{\textrm{d}x}\left(8x + \textrm{e}\right) = \frac{8}{8x+\textrm{e}}.](https://img.qammunity.org/2021/formulas/mathematics/college/grh9afxtnk7ojuyz37hoxryei9bb73kyol.png)
The ordinate of the point is
, so we evaluate:
![\frac{\textrm{d}f}{\textrm{d}x}\Big\vert_(x=0) = \frac{8}{8 * 0+\textrm{e}} = \frac{8}{\textrm{e}}.](https://img.qammunity.org/2021/formulas/mathematics/college/mcfynjs8cwni80yy9y09m92cd7059m07mt.png)
Finally:
![\frac{\textrm{d}f^(-1)}{\textrm{d}x}\Big\vert_(x=1) = \frac{1}{\frac{\textrm{d}f}{\textrm{d}x}\Big\vert_(x=f^(-1)(1))} = \frac{1}{\frac{\textrm{d}f}{\textrm{d}x}\Big\vert_(x=0)} = \frac{1}{\frac{8}{\textrm{e}}} = \frac{\textrm{e}}{8}.](https://img.qammunity.org/2021/formulas/mathematics/college/9dtsgbfu2d1z6yjiilaehpfpzruzq3qisr.png)
We can check the answer by finding the inverse:
![y = \ln(8x + \textrm{e}) \implies \textrm{e}^y = 8x + \textrm{e} \iff \textrm{e}^y - \textrm{e} = 8x \iff x = \frac{\textrm{e}^y-\textrm{e}}{8},](https://img.qammunity.org/2021/formulas/mathematics/college/dotr7r1zlcq4opudf4gixmzsedy86sidcf.png)
so that
![f^(-1)(x) = \frac{\textrm{e}^x-\textrm{e}}{8}.](https://img.qammunity.org/2021/formulas/mathematics/college/vn8yzwgg8a1oy0i8ecdvj1nconv4rw063e.png)
Therefore:
![\frac{\textrm{d}f^(-1)}{\textrm{d}x} = \frac{\textrm{e}^x}{8}.](https://img.qammunity.org/2021/formulas/mathematics/college/eenn0t27qq8joj7zkx69lvm6r2gm0t8o2n.png)
Which finally gives the same answer as before:
![\frac{\textrm{d}f^(-1)}{\textrm{d}x}\Big\vert_(x=1) = \frac{\textrm{e}^1}{8} = \frac{\textrm{e}}{8}.](https://img.qammunity.org/2021/formulas/mathematics/college/stpdm9vcpxkt6goyi06bcbhfbb1clgoyiz.png)
Answer:
![\boxed{\frac{\textrm{d}f^(-1)}{\textrm{d}x}\Big\vert_(x=1) = \frac{\textrm{e}}{8}}.](https://img.qammunity.org/2021/formulas/mathematics/college/kebl917qfk349siygeifk5p9th2w87zqql.png)